Variation in Growth and Wood Properties of Four Eucalyptus Species, their Hybrids and Clones in Vidarbha Region, Maharashtra, India - Kannan, K.; Bhandari, Suchita; Sivarajan, A. (Indian Forester, 2023)
Eucalyptus wood is major raw material for pulp and paper industry in India. This study was undertaken to identify superior genetic resources of Eucalyptus species viz E. urophylla, E. pellita, E. camaldulensis, and E. tereticornis and their hybrids in the Vidarbha region of Maharashtra. The trials were assessed for variability in height and Diameter at Breast Height from one to three years. Highly significant differences (p<0.05 to 0.0001) were found within and between the families (seed lots) and different species. Twenty-four best-performing trees were selected by using the index method and assessed for growth (HT, DBH, and MAI) and pulp properties. The wood density for the selected individuals and four check clones ranged from 405 Kg/m3 to 545 Kg/m3. Three progenies viz. UKPL EU33 (25.30 m3 ha-1 y-1), UKPL ET49 (23.13 m3 ha-1 y-1, and UKPL EC46 (20.86 m3 ha-1 y-1) were found to outperform the mean productivity of two control species (15.46 m3 ha-1 y-1). The higher pulp yield was observed in hybrids/clones of two species: E. urophylla and E. pellita. The two-hybrid combination; Uro-tereticornis) and Uro-camaldulensis expressed higher pulp yield (51.33 per cent and 49.82 per cent) with low kappa numbers (16.10 and 15.30) respectively. The selected individuals with higher growth, productivity and superior pulp properties may be used as parents for future breeding programs.